PAKET EDUKASI KESEHATAN PERTUMBUHAN DAN PERKEMBANGAN REMAJA DI HKBP PERUMNAS TANGERANG [ADOLESCENTS’ GROWTH AND DEVELOPMENT EDUCATION PACKAGE IN HKBP PERUMNAS TANGERANG] - Lia Kartika; Belet Lydia Ingrit; Riama Marlyn Sihombing; Ester Silitonga; Aktri Margaret Manihuruk (Universitas Pelita Harapan, 2019)
Children are the nation’s next generation. The transformation era and technology bring out enormous challenges for parents in achieving and maintaining children's health. Children may not realize that their bodies are worth for caring and nurturing because of their lack of information about the adolescents’ rapid physical, psychological, psychosocial, cognitive, moral, and spiritual development change. Various problems can arise throughout this adaptation process. The purpose of this community service was to increase the children’s knowledge on adolescent’s general growth and development, reproductive health for female participants and efforts to prevent injury for male participants. It also aimed to assess the nutritional status as an indicator of child’s normal growth. We found the increased of mean knowledge percentage of the male participants by 9.91% and female participants by 29.23% before and after providing education. The anthropometry results revealed that 56% of the male participants were in the normal range of the nutritional status. Nevertheless, 67,58% of female participants were in the poor nutritional status. At the end of the activity, participants were able to mention the health information that had been received and the efforts that had to be made to prevent health problems that could occur in their teenage years.